Relationship of glutenin loci and rye translocations with dough mixing properties of wheat grown in Colorado environments - Zheng, Shusong, author; Byrne, Patrick, advisor; Qian, Yaling, committee member; Seabourn, Bradford W., committee member; Haley, Scott D., committee member (Colorado State University. Libraries, 2007)
The unique breadmaking properties of wheat (Triticum aestivum L.) flour are largely determined by its glutenin proteins, encoded by genes at the Glu-1 and Glu-3 loci. Whereas the quality effects of the Glu-1 loci have been intensively studied, the effects of the Glu-3 loci are not fully understood. The wheat-rye (Secale cereale L.) chromosomal translocations 1AL.1RS and 1BL.1RS have been associated with a decrease in hard winter wheat breadmaking quality. This project was undertaken to evaluate the effects of glutenin allelic variation and rye translocations on dough rheology and to compare the effects between irrigated and dryland environments. We evaluated two populations in dryland and irrigated Colorado locations: (1) 190 recombinant inbred lines (RIL) from the cross between TAM 107-R7 and Arlin; and (2) a population of 96 cultivars and advanced lines, mainly from the U.S. Great Plains. Dough rheology was measured with a 10-g mixograph. Associations between genotype (glutenin loci and rye translocations) and phenotype (mixograph properties) were calculated with a simple t-test for the RIL population and a unified mixed model to reduce false positive associations for the cultivar population. Results indicated that (1) quality effects of glutenin loci and rye translocations were significantly affected by growing environments (P<0.05); (2) in the RIL population, poorer dough mixing properties were observed with Glu-Dla vs. Glu-Dld, Glu-Ala vs. Glu-Alb, Glu-Blc vs. Glu-Blb, Glu-A3e vs. Glu-A3c, and the combination of Glu-Ala/Glu-A3e vs. other allelic combinations at the Glu-Al and Glu-A3 loci; (3) in the cultivar population, Glu-Alc, Glu-Ble, Glu-Dla, and Glu-B3c and i were associated with poorer mixograph properties, whereas Glu-Alb, Glu-Blb, Glu-Dlb and d, and Glu-B3f and b were associated with higher values of mixograph properties; (4) the presence of IRS translocations was significantly (P<0.05) associated with lower values for most mixograph properties, with 1BL.1RS more detrimental than 1AL.1RS; Glu-Dld partially compensated for the negative effects of 1AL.1RS in the RIL population. These results suggest that selection of appropriate glutenin alleles and rye translocations can facilitate the development of cultivars with desirable dough rheology in wheat breeding programs in Colorado and similar environments.
Keywords: agronomy; plant sciences; food science